2017
DOI: 10.12738/estp.2017.5.0597
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Teachers’ Professional Self-Efficacy Beliefs in Terms of Their Perceived Autonomy Support and Attitudes towards the Teaching Profession: A Mixed Methods Study*

Abstract: The purpose of this study is to identify the probable factors that can contribute to prospective teachers' levels of professional self-efficacy beliefs. For this purpose, quantitative methods are used to measure their perceived autonomy support during undergraduate education, their attitudes towards the teaching profession, and their levels of professional self-efficacy beliefs, while qualitative methods were used to determine the factors affecting their professional self-efficacy beliefs. This study is carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
(41 reference statements)
2
6
0
Order By: Relevance
“…According to the sixth finding in the current study, a positive and significant correlation was found to exist between the teachers' attitudes toward the profession and their selfefficacy belief, and that teachers' self-efficacy belief positively predicted their attitude towards teaching. This finding coincides with several other studies in the literature (Ajmal et al, 2020;Bayrakdar et al, 2016;Cakmak et al, 2021;Cetin, 2016;Colomeischi & Colomeischi, 2014;Dadandi et al, 2016;Demirel & Akkoyunlu, 2010;Demirtas et al, 2011;Huang, 2020;Kanadli, 2017;Kara, 2020;Ozokcub, 2018b;Perren et al, 2017;Rimm-Kaufman & Sawyer, 2004;Sari et al, 2009;Ustuner, 2017;Yada et al, 2018). Moreover, in a study by Baltaci (2017), a positive and significant correlation was established between the selfefficacy beliefs and professional attitudes of teachers who serve as school principals, with similar results also found with candidate teacher by Kaleli (2020).…”
Section: Discussionsupporting
confidence: 92%
“…According to the sixth finding in the current study, a positive and significant correlation was found to exist between the teachers' attitudes toward the profession and their selfefficacy belief, and that teachers' self-efficacy belief positively predicted their attitude towards teaching. This finding coincides with several other studies in the literature (Ajmal et al, 2020;Bayrakdar et al, 2016;Cakmak et al, 2021;Cetin, 2016;Colomeischi & Colomeischi, 2014;Dadandi et al, 2016;Demirel & Akkoyunlu, 2010;Demirtas et al, 2011;Huang, 2020;Kanadli, 2017;Kara, 2020;Ozokcub, 2018b;Perren et al, 2017;Rimm-Kaufman & Sawyer, 2004;Sari et al, 2009;Ustuner, 2017;Yada et al, 2018). Moreover, in a study by Baltaci (2017), a positive and significant correlation was established between the selfefficacy beliefs and professional attitudes of teachers who serve as school principals, with similar results also found with candidate teacher by Kaleli (2020).…”
Section: Discussionsupporting
confidence: 92%
“…It was found to be high. This finding of the study matched up with the results of several studies that have been carried out on pre-service primary school teachers (AbouDagga, 2005;Aksoy, 2016;Alsheha, 1988;Babu & Raju, 2013;Baykara-Pehlivan, 2008;Çiğdem & Memiş, 2011;Baykara-Pehlivan, 2008;Bektaş & Nalçacı, 2012;Bulut, 2009;Dağ, 2010;Doğan & Çoban, 2009, Fadlelmula, 2015İlter, 2009;Kanadlı, 2017;Kerimgil Çelik, 2015;Kılıç & Bektaş, 2008;Korkmaz & Usta, 2010;Lašek & Wiesenbergová, 2007;Mehmood, Akhter, Ch, Hç., & Azam, 2013;Musa & Bichi, 2015;Özder, Konedralı, & Zeki, 2010;Özkan, 2017;Sarikaya, Töman, & Öztürk, 2018;Serin, Güneş, & Değirmenci, 2015;Sönmez, Işık, Sulak, 2017;Şen, 2006;Uğurlu & Polat, 2011;Yokuş, 2015).…”
Section: Discussionsupporting
confidence: 83%
“…To that extent, it proposes an original instrument that allows diagnosing the levels of knowledge, attitudes, and reasoning of future teachers on this subject. Comprehending teacher perceptions of media education is extremely useful because this subjectivity, according to the literature, is a predictor of how they can utilize certain media approaches or strategies in the classroom (Kanadlı, 2017;Mateus, 2016;Pegalajar-Palomino, 2015;Tondeur, van Braak, & Ertmer, 2017). Despite its importance, few instruments fulfill this purpose and those that exist tend to focus on the use of devices or exclusively on so-called digital competences (Tondeur et al, 2015).…”
Section: Introductionmentioning
confidence: 99%